2021
DOI: 10.1016/j.clnesp.2021.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Are we overfeeding hemodialysis patients with protein? Exploring an alternative method to estimate protein needs

Abstract: Background & aims: Sufficient protein intake is of great importance in hemodialysis (HD) patients, especially for maintaining muscle mass. Daily protein needs are generally estimated using bodyweight (BW), in which individual differences in body composition are not accounted for. As body protein mass is best represented by fat free mass (FFM), there is a rationale to apply FFM instead of BW. The agreement between both estimations is unclear. Therefore, the aim of this study is to compare protein needs based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
1
3
0
2
Order By: Relevance
“…Therefore, using targets set to LBM based on mathematical methods or TBW is likely to lead to significant over-or underdosing of protein in all other groups. This is in line with findings in other patient categories [16,18].…”
Section: Protein Provision Icusupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, using targets set to LBM based on mathematical methods or TBW is likely to lead to significant over-or underdosing of protein in all other groups. This is in line with findings in other patient categories [16,18].…”
Section: Protein Provision Icusupporting
confidence: 93%
“…Thus, the LBM 27.5 method becomes more realistic as actual BMI increases (up to a certain point), explaining the proportional bias that can be seen in Fig. 1 adjusted to BMI ¼ 27.5) in 115 hemodialysis patients and concluded that mean protein needs estimated by (adjusted) TBW were higher than those based on LBM BIA , across all BMI categories (P < .01), and most explicitly in obese patients [18]. This overestimation occurred eventhough a correction factor in grams/kg was used (LBM BIA * 1.5, whereas (adjusted) TBW * 1.2).…”
Section: Breaking Down the Biasmentioning
confidence: 93%
“…Two articles were published and discussed comparing protein requirements calculation based on bodyweight and FFM. In both studies, a large underand overestimation in protein requirements was seen when using bodyweight, especially in participants with under-and overweight [8,9]. To continue this discussion, the answer is sought in a large population to the following question: Will choosing actual bodyweight, corrected bodyweight or FFM to calculate protein requirements result in clinically relevant differences?…”
Section: Introductionmentioning
confidence: 99%
“…In Ermangelung einer wirklichen Referenz (=die Bestimmung des tatsächlichen Proteinbedarfs anhand einer systematischen Analyse der Stickstoffbilanz) ist die Bedeutung der mitgeteilten Ergebnisse zunächst endlich. Allerdings ist die untersuchte Fragestellung bisher wenig beachtet worden: die Autor*innen verweisen auf lediglich 3 Studien, die bisher zu diesem Thema publiziert worden sind 2 3 4 , eine weitere Studie haben sie übersehen 5 .…”
Section: Kommentarunclassified
“…In dieser Studie wurde der Proteinbedarf mit 1,2 g/kg Körpergewicht (bzw. bei Untergewicht und Adipositas mit dem jeweils korrigierten Körpergewicht) und [2][3][4], eine weitere Studie haben sie übersehen [5].…”
unclassified